Animal genetic resources data banks - Trail, J.C.M. (Food and Agriculture Organization of the United Nations, 1984)
Describes the information and documentation services at ILCA headquarters in relation to information dissemination and the service by ILCA on data analyses and interpretation for national research organizations. Gives examples of importand breed groups.